ANALISIS YURIDIS ATAS PENDAPAT HAKIM TENTANG PERCERAIAN DENGAN ALASAN PERSELINGKUHAN (Studi Putusan Pengadilan Agama Malang Nomor 1403/Pdt.G/2020/Pa.Mlg) - rofik kurohhman (Dinamika, 2022)
ABSTRACTMarriage is done forever until the end of life, this is what husband and wife want. However, there are certain circumstances that are a factor in the occurrence of divorce. Cheating acts results in disharmony in the rift of the household itself and has a negative effect on other people’s household. However, the reasons for divorce are not regulated in Law No. 1 of 1974 concerning Marriage, but are applied in Article 19 of PP No. 9 of 1975. The purpose of this paper is to find out the legal basis used by the judges of the Malang Religious Court and to know the consideration in deciding cases on the grounds of infidelity. The type of research used is normative juridical by examining library materials or secondary data. The legal basis used by judges in deciding cases is based on Article 1 and Article 33 of Law No. 1 of 1974 jo. Article 3 and Article 77 of the KHI as well as article 19 (f) PP No. 9 of 1975 jo. Article 116 (f) KHI. The judge’s consideration in deciding the case is the Supreme Court Jurisprudence No. 38 of 1990.Key Words: Judges Opinion, Divorce, AffairABSTRAKPerkawinan dilakukan untuk selamanya hingga akhir hayat, inilah yang diinginkan suami istri. Namun keadaan tertentu ada beberapa yang menjadi faktor terjadinya perceraian. Perbuatan selingkuh mengakibatkan ketidakharmonisan keretakan rumah tangga itu sendiri dan berefek negatif bagi rumah tangga orang lain. Tetapi alasan perceraian tidak diatur dalam UU No.1 Tahun 1974 Tentang Perkawinan, namun diterapkan dalam pasal 19 PP No 9 Tahun 1975. Tujuan Penulisan ini ingin mengetahui dasar hukum yang digunakan oleh hakim Pengadilan Agama Malang serta mengetahui pertimbangan dalam memutus perkara dengan alasan perselingkuan. Jenis peneltian yang digunakan adalah yuridis normatif dengan meneliti bahan pustaka atau data sekunder. Dasar hukum yang digunakan hakim dalam memutus perkara berdasarkan pasal 1 dan pasal 33 UU No 1 Tahun 1974 jo. Pasal 3 dan pasal 77 KHI serta pasal 19 (f) PP No 9 Tahun 1975 jo. Pasal 116 (f) KHI. Pertimbangan hakim dalam memutuskan perkara adalah Yuriprudensi MA No 38 Tahun 1990.Kata Kunci: Pendapat Hakim, Perceraian, Perselingkuhan